Analysis of the Influence of Social Media Marketing on Glad2Glow Skincare Purchase Decisions through Celebrity Endorsers - Muhammad Saddam Navaro; Bayu Hari Prasojo; Alshaf Pebrianggara; Mochamad Rizal Yulianto (Transpublika Publisher, 2025)
The Indonesian skincare industry has experienced rapid growth, driven by increasing consumer awareness of skin health and a strong inclination toward trends promoted on digital platforms. Among emerging local brands, Glad2Glow has leveraged social media marketing and celebrity endorsements to enhance visibility and consumer engagement. This study aims to analyze the influence of Social Media Marketing and Celebrity Endorser on Purchase Decision of Glad2Glow skincare products. This research employed a quantitative approach using an online questionnaire survey distributed to Glad2Glow product users in Indonesia. Data analysis was carried out using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 software. The results reveal that Social Media Marketing has a positive and significant effect on Purchase Decision, and similarly, Celebrity Endorser also has a positive and significant effect on Purchase Decision. These findings shed light that social media marketing strategies combined with celebrity endorsement can effectively enhance consumer interest and purchasing decisions for Glad2Glow products.